(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The agnostic intellectual Arnold could never fully gothrough the poetic inspiration of the Romantics like Wordsworth and Keats, manyof whose sentiments and imagery he echoed. It is romantic melancholia whichbrought out the best of his artistic power. He was by nature and temperamentsuited to write elegiac poems and in English literature there is no worthycompetitor to him in this particular genre. Extremely sensitive to any kind ofloss, personal or general, Arnold had the capacity to express his griefgracefully and poignantly, with sincerity and an adequately restrained passion.The combination of a romantic urge and a classical taste has given Arnold anexceptional superimacy in the field of elegy.